Evaluación de un proceso para la obtención de fitoesteroles partiendo de la semilla del aguacate (Persea americana Mill. Var Hass) a escala laboratorio (2019)
In order to carry out the extraction of phytosterols from avocado seeds (Persea americana Mill. Var Hass), a bibliographic search was conducted in the first instance regarding the operating conditions for the extraction of oil from the mentioned seed using three Methodologies: Soxhlet extraction, ultrasound-assisted extraction and microwave-assisted extraction, this pre-experiment was carried out taking into account that the stability of the oil, its nutritional value and, consequently, the profile of phytosterols, depends not only on environmental factors and genetic of the cultivation of the fruit but also of the extractive process used; the review in the literature allowed establishing the appropriate conditions for the mentioned methodologies using an environmentally friendly solvent, such as ethanol. However, according to the selection of parameters performed, the tests for ultrasound and microwave methodologies were poorly reproducible with almost zero amounts of oil, so the technique selected corresponded to soxhlet, with which an oil yield of 10,623 % was obtained from 25 g of ground seed, using a sample ratio: solvent equivalent to 1:10, a temperature of 70 ° C, an extraction time of 6 hours and a particle size of 0.59436 mm (mesh No. 30).